Conceptual system of the German folk tale - Puty, O. S. (Cognition, Communication, Discourse, 2018)
This paper presents a model of the conceptual space of the German fairy-tale discourse based on the results of the quantitative and interpretative analysis. It reveals a set of dominant concepts and regularities of their combinability.